EXPANSION OF TRINUCLEOTIDE REPEATS IN HUMAN DNA AND MOLECULAR DIAGNOSIS OF TRINUCLEOTIDE EXPANSION DISORDERS: INTEGRATIVE REVIEW: Molecular diagnosis of TNR expansion disorders - Pedrosa, Andre; Borges Filho, Leoncio Rabelo (Acta Biologica Brasiliensia, 2024)
Trinucleotide repeat (TNR) expansions are increases in the number of repeated trinucleotides in the genome. TNR expansions have been confirmed as the molecular etiology of various neurodegenerative disorders, such as Huntington's Disease, Fragile X Syndrome, and Friedreich's Ataxia. Due to the potential achieved by molecular diagnostic technology, new disorders related to TNR expansions are being elucidated more rapidly, as high-throughput technologies for analyzing DNA are described every year. Thus, we carried out an integrative review on the importance of improving DNA analysis methods for the molecular diagnosis of diseases related to TNR expansions. We searched the PubMed using the descriptors "trinucleotide expansion", "DNA analysis", "genome" and "DNA sequencing". In our review, 42 genomic targets were identified as being responsible for diseases related to TNR expansions, with one target being related to two diseases and two targets being related to three diseases. The rest of the targets are related to a single disease. Despite the emergence of new sequencing technologies, PCR-based techniques continue to play an important role in identifying targets related to diseases caused by TNR expansions. New DNA sequencing technologies have demonstrated an important contribution to the identification of targets related to diseases caused by TNR, especially since 2019. The development of novel DNA analysis techniques and new genomic analysis tools has the potential to unveil novel targets associated with TNR expansions.